Pharmacology and early ADMET data of corallopyronin A, a natural product with macrofilaricidal anti-wolbachial activity in filarial nematodes - Ehrens, Alexandra; Schiefer, Andrea; Krome, Anna K.; Becker, Tim; Rox, Katharina; Neufeld, Helene; Aden, Tilman; Wagner, Karl G.; Müller, Rolf; Grosse, Miriam; Stadler, Marc; König, Gabriele M.; et al. (Frontiers in Tropical Diseases, 2022)
Corallopyronin A (CorA), a natural product antibiotic of Corallococcus coralloides, inhibits the bacterial DNA-dependent RNA polymerase. It is active against the essential Wolbachia endobacteria of filarial nematodes, preventing development, causing sterility and killing adult worms. CorA is being developed to treat the neglected tropical diseases onchocerciasis and lymphatic filariasis caused by Wolbachia-containing filariae. For this, we have completed standard Absorption, Distribution, Metabolism, Excretion and Toxicity (ADMET) studies. In Caco-2 assays, CorA had good adsorption values, predicting good transport from the intestines, but may be subject to active efflux. In fed-state simulated human intestinal fluid (pH 5.0), CorA half-life was >139 minutes, equivalent to the stability in buffer (pH 7.4). CorA plasma-stability was >240 minutes, with plasma protein binding >98% in human, mouse, rat, dog, mini-pig and monkey plasma. Clearance in human and dog liver microsomes was low (35.2 and 42 µl/min/mg, respectively). CorA was mainly metabolized via phase I reactions, i.e., oxidation, and to a minimal extent via phase II reactions. In contrast to rifampicin, CorA does not induce CYP3A4 resulting in a lower drug-drug-interaction potential. Apart from inhibition of CYP2C9, no impact of CorA on enzymes of the CYP450 system was detected. Off-target profiling resulted in three hits (inhibition/activation) for the A3 and PPARγ receptors and COX1 enzyme; thus, potential drug-drug interactions could occur with antidiabetic medications, COX2 inhibitors, angiotensin AT1 receptor antagonists, vitamin K-antagonists, and antidepressants. In vivo pharmacokinetic studies in Mongolian gerbils and rats demonstrated excellent intraperitoneal and oral bioavailability (100%) with fast absorption and high distribution in plasma. No significant hERG inhibition was detected and no phototoxicity was seen. CorA did not induce gene mutations in bacteria (Ames test) nor chromosomal damage in human lymphocytes (micronucleus test). Thus, CorA possesses an acceptable in vitro early ADMET profile; supported by previous in vivo experiments in mice, rats and Mongolian gerbils in which all animals tolerated CorA daily administration for 7-28 days. The non-GLP package will guide selection and planning of regulatory-conform GLP models prior to a first-into-human study.